2007
DOI: 10.2307/40035862
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Strategies and Geochemical Characterization of Lithic Assemblages: A Comparison of Three Case Studies from Western North America

Abstract: Based on a simple model of lithic procurement, reduction, and use, we generate predictions for patterns in source diversity and average distance-to-source measurements for flaked stone assemblages left behind by small-scale and residentially mobile populations. We apply this model to geochemical data from obsidian artifacts from three regions in western North America. As predicted, results show markedly different patterns in the geochemical composition of small flakes, large flakes, and formal tools. While sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 43 publications
1
36
0
1
Order By: Relevance
“…This analysis is proving to be quite promising. Others have used debitage sizes to help determine aboriginal land-use practices (Baumler and Davis 2004;Eerkens et al 2007). Inferences derived from debitage are often made from a population or assemblage of debitage specimens.…”
Section: Debitage Individuals and Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis is proving to be quite promising. Others have used debitage sizes to help determine aboriginal land-use practices (Baumler and Davis 2004;Eerkens et al 2007). Inferences derived from debitage are often made from a population or assemblage of debitage specimens.…”
Section: Debitage Individuals and Aggregatesmentioning
confidence: 99%
“…Obsidian sources have been widely assessed geochemically and have proven to be fairly reliably linked to archaeological specimens (Bayman and Shackley 1999;Eerkens and Glascock 2000;Eerkens et al 2007;Ferguson and Skinner 2005;Glascock et al 1994;Hughes 1998;Negash et al 2006Negash et al , 2007Roth 2000;Shackley 1998bShackley , 2005Stoltman and Hughes 2004;Tykot 2002Tykot , 2003. Some obsidian provenience studies have been able to reliably recognize ''subsources'' of obsidian and have shown that these sources provide useful information related to human land-use practices (Eerkens and Rosenthal 2004;Young 2002).…”
Section: Raw Materials and Organizational Choicesmentioning
confidence: 99%
“…In the case of chert, characterization can be approached on the basis of different visual macrogeological features (i.e., color, aspect, transparency, fracture, presence of inclusions, etc.). This visual approach has thus far proven insufficient, however, and in recent years additional criteria have been applied to characterize siliceous rocks including sedimentary petrography (Séronie-Vivien & Séronie-Vivien, 1987;Delange, 2003;Odell, 2004) and geochemical analysis (McDonnell, Kars, & Jansen, 1997;Malyk-Selivanova et al, 1998;Bressy, 2003;Eerkens et al, 2007;Milne, Hamilton, & Fayek, 2009). Unfortunately, most of these methodologies entail a major disadvantage: the partial destruction of the archaeological piece.…”
Section: Introductionmentioning
confidence: 99%
“…From this we can learn about the formation and depositional contexts of various lithic raw materials so as to begin to define specific source areas (Leudtke, 1992:39). The use of geochemical and mineralogical approaches to characterize the elemental and mineralogical composition of lithic materials has gained momentum in archaeology over the last several decades (e.g., Eerkens et al, 2007;Evans et al, 2007;Hull et al, 2008;Hess, 1996;Hoard et al, 1992Hoard et al, , 1993Jarvis, 1988;Leudtke, 1978Leudtke, , 1979Morrow et al, 1992;Malyk-Selivanova et al, 1998;Norman et al, 1989;Speilbauer, 1984). Those approaches most commonly used in chert sourcing studies are X-ray fluorescence (XRF), X-ray diffraction (XRD), instrumental neutron activation analysis (INAA), and inductively coupled plasma (ICP).…”
Section: Sourcing Chert: Visual Vs Geochemical and Mineralogical Appmentioning
confidence: 99%
“…Therefore, both SIMS and LA-ICP-MS are minimally destructive since they require very small samples (ϳ1 mm). [XRF is also relatively nondestructive; however, it is a bulk analytical technique (Eerkens et al, 2007).] Finally, unlike INAA, SIMS samples do not require any special post-analysis curation since they are not rendered radioactive upon completion of their study (Church, 1994:51).…”
Section: Sourcing Chert: Visual Vs Geochemical and Mineralogical Appmentioning
confidence: 99%